To assess community care services effectiveness: the use of the Chronic Obstructive Pulmonary Disease in-patient admission rate (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundAssessment of appropriateness is a criteria of increasing relevance for delivering health care services. In Italy elderly hospital admissions for Chronic Obstructive Pulmonary (COPD) disease is one of the chosen indicators to measure the appropriate use of services. This study describes the characteristics of hospital admissions at a regional level for COPD – DRG 88 and to evaluates their relationship with other indicators linked to the provision of hospital or community care services.MethodsData on hospital admissions for COPD in the years 2006 and 2011 were collected from hospital discharge records. Correlations among acute in-patients admission rates by Italy’s Regions and provision of Long Term Care (LTC) services have been analyzed through univariate and multivariate linear regression models.ResultsThe national rate of hospitalization for COPD decreased from 2006 to 2011 (-35%). The COPD in-patient admission rate showed a weak inverse relation with the provision of LTC that was statistically significant only for 65-74 age-group in 2006. The reduction was greater than 60% for those under the age of 75 and around 14% for those over 74 years.The inclusion in the interpretative model the rate of beds per capita in and the rate of General Practitioners improves the percentage of variability between the regions in the rate of hospitalization for the DRG 88 explained by the model itself.ConclusionThe reduction in hospitalizations for COPD in the over-fifty age group is particularly noticeable; it seems mainly related to factors other than to the operation of those services outside the hospital.